Impact of chemotherapy followed by aromatase inhibitors on bone health of women with ER-positive early breast cancer in real world clinical settings in Greece: Results of the POCHARBI trial conducted by the Hellenic Society of Breast Surgeons. (June 2016) - Markopoulos, C.; Koukouras, D.; Venizelos, V.; Karyda, I.; Xepapadakis, G.; Misitzis, J.; Kalogerakos, K.; Poulakaki, F.; Natsiopoulos, J.; Zobolas, V.; Savidou, C.; Antonopoulou, Z.; et al.
Abstract: Introduction: The aim of this observational study was to assess the combined impact of chemotherapy (CT) and aromatase inhibitors (AI) therapy on bone mineral density (BMD) in postmenopausal women with estrogen receptor (ER)-positive early breast cancer. Methods: Patients were treated with a third generation AI, either as adjuvant therapy (HT cohort, n = 166) or as subsequent endocrine therapy after initial treatment with chemotherapy (CT cohort, n = 124), and were followed up for a 12-month period. BMD was evaluated at lumbar spine (LS) and total hip (HP) before CT, before AI therapy and after 12 months of AI therapy. The primary study objective was changes in LS BMD between pre CT treatment and post 12 months AI therapy in the CT cohort. Results: There were no statistically significant changes in LS BMD, either within CT or HT cohort. In the CT cohort, the mean LS BMD change was −0.72% (95% CI: −2.97%, +1.53%, p = 0.5526) between CT start and month 12 of AI therapy, while it was −0.19% (95% CI: −2.12%, +1.74%, p = 0.8309) and −0.59% (95% CI: −3.18%, +2.00%, p = 0.4759) between CT start and AI start and AI start and month 12 of AI therapy respectively. The mean change in LS BMD in the HT cohort (i.e. after 12 months of AI treatment) was +1.51% (95% CI: −0.96%, +3.98%, p = 0.7420). Conclusions: The results of this study indicate that, under routine clinical practice, most postmenopausal patients who receive CT before AI therapy do not experience debilitating BMD consequences during the first year of AI treatment. Trial registration : ClinicalTrials.gov IdentifierNCT01298362 . Highlights: Estrogen deprivation caused by AI administration has a serious negative effect on bone health. Calcium and Vitamin-D, as well as antiresoptive agents might be used in order to prevent bone loss. Patients who receive CT before AI therapy do not experience debilitating BMD consequences.